Fertilização e desenvolvimento embrionário: Morfometria e análise estereomicroscópica dos ovos dos híbridos de surubins (pintado, Pseudoplatystoma corruscans x cachara, Pseudoplatystoma fasciatum) - Faustino, Francine; Nakaghi, Laura Satiko Okada [UNESP]; Marques, Camila [UNESP]; Makino, Lilian Cristina [UNESP]; Senhorini, José Augusto (Universidade Estadual de Maringa, 2007)
This study aimed to analyze the morphometry of hybrids' eggs under stereomicroscopy. The induced reproduction was carried out in specimens of pintado's females (P. corruscans) and cachara's males (P. fasciatum) from Cepta - Ibama, Pirassununga, state of São Paulo, Brazil. Samples were collected in extrusion moment, during the fertilization, in times of 10 and 30 seconds, 1, 2, 5, 8, 10, 15, 20, 30 and 45 minutes, 1 hour, at every 15 minutes until completing 2 hours, and afterwards, at every hour until the larval hatching. Oocytes and eggs' external morphology were observed, photographed and 30 samples from each moment were measured in stereomicroscopy. Oocytes, in the time of extrusion, and the eggs presented a spherical form and yellowish color. Characteristics such as wide perivitelinic space, somites, presence of optical vesicle and the main phases of embryonic development as egg-cell (blastodisc), 2, 4, 8, 16, 32 and 64 blastomeres, morula, blastula, gastrula, epiboly movements, formation and larvae hatching were verified.
Fertilization and embrionary development: Morphometry and stereomicroscopic analysis of hybrids' eggs from surubins (pintado, Pseudoplatystoma corruscans and cachara, Pseudoplatystoma fasciatum)
Keywords: Embriogenesis; Hybrid; Morphometry; Surubins; animal cell; animal experiment; blastomere; blastula; cachara; controlled study; embryo development; female; fish; gastrula; hatching; male; morphometrics; morula; nonhuman; oocyte; Pseudoplatystoma corruscans; pseudoplatystoma fasciatum; somite; stereomicroscopy; Pseudoplatystoma fasciatum